Efficient pricing of electricity revisited - Mathias Mier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
Increasing shares of intermittent renewable energies challenge the dominant way to trade electricity ex-ante in forward, day-ahead, and intraday markets: Coal power plants and consumers cannot react to the stochastic element of renewables, whereas gas turbines can. We use a theoretical model to analyze consumer behavior and incentives of perfectly competitive firms to invest in different types of technologies under ex-ante pricing. Curtailed consumers need to get subsidized in high of their disruption cost. Coal power firms recover cost. Renewables and gas turbine firms fail to do so. We identify imperfections that arise from the delay in price setting and market clearing. Do real-time prices induce an efficient outcome? Consumers need to get taxed in high of rationing cost. Support is redundant for gas turbine firms, but renewables firms still fail to recover cost because they cannot ensure against their price risk.
Keywords: D41; D47; Q41; Q48; L94; L98; 330; efficient pricing; market design; capacity mechanisms; renewable energies; supply uncertainty; consumer behavior